HUBUNGAN RIWAYAT HIPERTENSI PADA IBU HAMIL DENGAN KEJADIAN PREEKLAMPSIA DI RUMAH SAKIT IBU DAN ANAK (RSIA) BANDA ACEH - Devi Fasrah; Teuku Adtya Kemal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Preeclampsia is a major cause of perinatal morbidity and mortality in Indonesia.One of the causes of preeclampsia is the history of hypertension, which has experienced hypertension before pregnancy or before 20 weeks of pregnancy.Mothers who have a history of hypertension are at greater risk of experiencing preeclampsia, so the risk of maternal and neonatal morbidity and mortality is higher.This research aimed to determine the relationship between the history of hypertension and the incidence of preeclampsia at the Mother and Child Hospital, Banda Aceh. This type of research is descriptive-analytic using a cross-sectional study design.The population in this study was pregnant women in the Midwifery and Delivery Room of the Mother and Child Hospital, Banda Aceh, with 33 samples.Sampling is done by total sampling technique using medical record data.The results showed that 19 respondents (57.6%) were in the age range of 30-40 years old; 24 respondents (72.7%) had severe preeclampsia; and 24 respondents (72.7%) had no history of hypertension.The conclusion of this research showed that there was a relationship of hypertension history with the incidence of preeclampsia in Mother and Child Hospital, Banda Aceh, with ρ-value=0.031.According to the research result, it is expected that health services can increase public education about factors that can influence the incidence of preeclampsia.Keywords: Preeclampsia, history of hypertension, pregnant women